2018
DOI: 10.1177/0333102418791818
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the characteristics of headache due to unruptured intracranial vertebral artery dissection

Abstract: Background and purpose It is sometimes difficult to diagnose intracranial vertebral artery dissection in patients with headache as the only symptom. Knowledge of the characteristics of the headache would facilitate the diagnosis. In this study, we aimed to clarify the characteristics of intracranial vertebral artery dissection-related headache using our original self-administered questionnaire. Methods Via the questionnaire, we ascertained headache characteristics and investigated whether they differed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In both entities, a lesion of the ascending pathways of the trigeminal nuclei is mostly the cause, next to damage to the cervical spinothalamic pathways or cortical processing areas. Another cause of facial pain is cervical carotid or vertebral artery dissection [62]. The facial pain is usually ipsilateral to the side of the dissected vessel and mostly of sudden onset.…”
Section: Central Causes Of Facial Painmentioning
confidence: 99%
“…In both entities, a lesion of the ascending pathways of the trigeminal nuclei is mostly the cause, next to damage to the cervical spinothalamic pathways or cortical processing areas. Another cause of facial pain is cervical carotid or vertebral artery dissection [62]. The facial pain is usually ipsilateral to the side of the dissected vessel and mostly of sudden onset.…”
Section: Central Causes Of Facial Painmentioning
confidence: 99%
“…Our study Shibahara [12] Matsumoto [16] Acute pain 89. pain onset in the headache group, and on day 51 in the infarction group. All changes started before 3rd month and ended after 6 to 7 months when the image tracking period was limited to 1 year or less (Figs.…”
Section: Characteristics (%)mentioning
confidence: 76%
“…Headache is the common symptom in patients with cervical artery dissection (CAD), but the characteristics of pain associated with CAD are not specific and can sometimes resemble migraine or even cluster headache (2). A recent study showed that more specific headache characteristics in patients with intracranial vertebral artery dissection included: headache in the occipitonuchal region, with unilateral, pulsatile and acute onset, with severe intensity, and without nausea or vomiting (8). .…”
Section: Resultsmentioning
confidence: 99%